Новые данные о находке византийского меча на территории Харьковской области = Novyye dannyye o nakhodke vizantiyskogo mecha na territorii Khar’kovskoy oblasti - БАРАНОВ, Геннадий (Historia i Świat, 2019)
The article introduces new data which is connected to the found of a Byzantine sword in the Kharkov region of Ukraine. Previously, it was assumed that the sword was found on the territory of Sukhogomolshansky cremation grave field, but today it is proven that the sword originates from a cremation grave of the grave field near the village Kitsevka. Probably, this sword should be connected to the diplomatic relations between the Byzantine Empire and the Khazar Kaghanate.